- MARKETING MANAGEMENT GUIDELINES FOR THE COMPLETE SUPPLEMENT MANUFACTURING BUSINESS IN MUANG SAMUT SAKHON DISTRICT - Worapongpat, Ntapat (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2021)
This research is a qualitative research on marketing management guidelines for complete supplementary food manufacturing business in Muang Samut Sakhon district with the objectives as follows: 1) to study the opinions of consumers on the condition of marketing management for the complete supplementary food manufacturing business in Muang Samut Sakhon district; 2) to study the recommendations on marketing management of the complete supplementary food business in Muang Samut Sakhon district and 3) to find guidelines for marketing management of the complete supplementary food business in Muang Samut Sakhon district. The sample group in the study was 400 consumers who ordered or purchased service of the complete supplementary food manufacturing business in Muang Samut Sakhon district obtained by simple random sampling. The research tool was a questionnaire and the statistics used to analyze the data were percentage, mean and standard deviation. The results of the study found that most of the samples were aged 25-35 years with a bachelor’s degree and monthly income in the range of 100,001- 200,000 baht. The study of marketing management factors influencing the order to manufacture food supplementary revealed that the product factor, distribution channel and sales promotion had an influence on the marketing management guidelines for the complete supplementary food manufacturing business in Muang Samut Sakhon district accounted for 48.5%. The remaining 51.5% was due to price variables which had negative influence on marketing management for complete supplementary food manufacturing business in Muang Samut Sakhon district.